Effectiveness of High-Fidelity Simulation on Creative Clinical Reasoning Among Nursing Students: A Quasi-Experimental Study - Danniel Hilman Maulana; Karina Chandra; Maria Rodriguez (Enigma in Education, 2025)
High-fidelity simulation has become a key pedagogical strategy in nursing education, yet its specific effect on creative clinical reasoning remains underexplored, particularly in Southeast Asian higher-education contexts. The aim of this study was to evaluate the effectiveness of high-fidelity simulation on creative clinical reasoning, clinical judgment, and self-efficacy among nursing students. This quasi-experimental pre-test/post-test control group study, conducted at a private university in Palembang, Indonesia, evaluated its effectiveness among ninety final-year nursing students allocated to a simulation group (n=46) receiving four structured high-fidelity simulation sessions over eight weeks or a control group (n=44) receiving conventional case-based learning. Outcomes were measured using the Health Sciences Reasoning Test, a Creative Clinical Problem-Solving Scale, the Lasater Clinical Judgment Rubric, and the General Self-Efficacy Scale, with all scores standardized to a 0–100 metric, and analyzed using paired t-tests, independent t-tests, and ANCOVA with pre-test covariates. The simulation group demonstrated significantly greater improvements than controls in clinical reasoning (mean difference 16.2, 95% CI 13.8–18.6, p<0.001, Cohen’s d=1.98), creative problem-solving (15.5, p<0.001, d=2.10), self-efficacy (14.5, p<0.001, d=1.73), and clinical judgment (16.3, p<0.001, d=2.12); ANCOVA confirmed significant group effects (partial η²=0.322–0.375), and a positive dose-response correlation was observed (r=0.72, p<0.001). High-fidelity simulation was highly effective in enhancing creative clinical reasoning and related competencies, with large effect sizes supporting its systematic integration into nursing education curricula.